Healthy Eating Limitations: A Qualitative Analysis of Emerging Semantics in School Communities of Ciudad Sur; [Barreras Para Una Alimentación Saludable: Un Análisis Cualitativo de Las Semánticas Emergentes en Las Comunidades Escolares de Ciudad Sur] - Saez-Tonacca, L; Palacios-Pino, J; Diaz-Ramirez, C; Pizarro-Quevedo, T (Sociedad Chilena de Nutricion Bromatologia y Toxilogica, 2024)
Literature has emphasized on food environments centrality in food choices and nutritional status. Objective: identify social perceptions of fathers, mo-thers and guardians, professionals from educational establishments, municipal officials, and stallholders belonging to the southern area of Santiago de Chile, regarding limitations of healthy diet implementation on school environments. Method: six focus groups were carried out grouping 50 key actors linked to educational establishments using a non-probabilistic sample. A content analysis was applied through thematic coding technique seeking to reveal emerging semantic universes. Results: Nine barriers, or semantics, were identified characterizing limitations to healthy eating habits in school environments: family, school kiosks, leaving school establishments, taste, socioeconomic determinants, public policy, lack of knowledge, publicity, and availability of products without seals. Conclusions: limitations associated with domestic food environment have a significantly high representation (47,9%) and contain an individualized responsibility feature. This explanatory culture is opposed to scientific and academic evidence regarding the functioning of eating behavior, and the centrality of food environments facilitating or hindering healthy food consumption. © 2024 Sociedad Chilena de Nutrición, Bromatología y Toxicología. Este es un artículo open access bajo la licencia CC BY-NC-ND. Publicado por.